2019
DOI: 10.1002/ana.25457
|View full text |Cite
|
Sign up to set email alerts
|

AZATAX: Acetazolamide safety and efficacy in cerebellar syndrome in PMM2 congenital disorder of glycosylation (PMM2‐CDG)

Abstract: Objective: Phosphomannomutase deficiency (PMM2 congenital disorder of glycosylation [PMM2-CDG]) causes cerebellar syndrome and strokelike episodes (SLEs). SLEs are also described in patients with gain-of-function mutations in the CaV2.1 channel, for which acetazolamide therapy is suggested. Impairment in N-glycosylation of CaV2.1 promotes gain-of-function effects and may participate in cerebellar syndrome in PMM2-CDG. AZATAX was designed to establish whether acetazolamide is safe and improves cerebellar syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 45 publications
0
39
0
Order By: Relevance
“…Defects in the glycosylphosphatidylinositol (GPI)-anchor synthesis have more recently been added to this family [ 4 ]. CDG are mainly complex, multi-system disorders which—despite recent exciting therapeutic developments—still widely lack effective treatments [ 5 , 6 , 7 , 8 , 9 , 10 ]. PMM2-CDG (MIM: 212065) was the first reported N-glycosylation defect and it is the most common type with approximately 1000 patients reported worldwide [ 5 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Defects in the glycosylphosphatidylinositol (GPI)-anchor synthesis have more recently been added to this family [ 4 ]. CDG are mainly complex, multi-system disorders which—despite recent exciting therapeutic developments—still widely lack effective treatments [ 5 , 6 , 7 , 8 , 9 , 10 ]. PMM2-CDG (MIM: 212065) was the first reported N-glycosylation defect and it is the most common type with approximately 1000 patients reported worldwide [ 5 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…No curative treatment has been developed. A recent trial with acetazolamide, a long-known diuretic, showed a significant improvement of the motor cerebellar syndrome in PMM2-CDG [ 20 ]. This is a nice example of drug repositioning.…”
Section: Discussionmentioning
confidence: 99%
“…Acetazolamide shows efficacy in treating SLEs in CACNA1A familial hemiplegic migraine. 10,71 Remarkably, in PMM2 patients, coagulation parameters show improvement in addition to neurologic involvement. Enzymatic activity of PMM2 is dependent on Ca 2+ binding.…”
Section: Other Approachesmentioning
confidence: 97%
“…Recent reports demonstrated beneficial effects of acetazolamide in PMM2-CDG. 10 In patients with spasticity or dystonia, local injection of botulinum toxin may be useful. Aggressive treatment of increased body temperature (escalating fever), which often exacerbates seizures, myoclonus, and other movement disorders, and may provoke stroke-like episodes in many patients, is essential.…”
Section: Neurologic Involvementmentioning
confidence: 99%
See 1 more Smart Citation